Oral health care challenges in individuals with severe mental illness: a qualitative meta-synthesis - Afroz, Tanzina; Beyene, Joseph; Zaheer, Khaleda; Alameddine, Mohamad; Nabi, Mohammad Hayatun; Hawlader, Mohammad Delwer Hossain; Hossain, Ahmed (Frontiers in Oral Health, 2025)
BackgroundIndividuals with severe mental illness (SMI) experience significantly higher rates of poor oral health, including dental caries, periodontal disease, and edentulism, compared to the general population. This meta-synthesis investigates the challenges faced by individuals with SMI in managing oral health and potential solutions.MethodsA comprehensive literature search (2010–2024) was conducted across PubMed, Web of Science, Scopus, and Google Scholar for any-language studies. The meta-synthesis involved systematic article selection, quality appraisal, and thematic data extraction/synthesis.ResultsFrom 1,698 records, 101 full-text articles were reviewed; 11 met the inclusion criteria. Findings consistently demonstrate a high prevalence of poor oral health outcomes (caries, tooth loss, periodontal disease) among individuals with SMI, alongside significantly lower engagement in oral hygiene (e.g., toothbrushing) and dental care-seeking behaviours. Key barriers include financial constraints, dental anxiety, medication side effects (notably xerostomia), and low oral health awareness. Stigma and inadequate dental professional training in mental health further impede access. Proposed solutions emphasise integrating oral health education into psychiatric rehabilitation, enhancing communication between dental and mental health providers, and developing tailored support systems. Evidence suggests a bidirectional relationship between oral and mental health.ConclusionThis meta-synthesis confirms a stark oral health disparity for individuals with SMI, driven by suboptimal hygiene, medication effects, limited health literacy, and formidable access barriers compounded by financial hardship and stigma. Addressing this requires urgent, coordinated integration of mental and oral healthcare through co-located services, interdisciplinary collaboration, and tailored interventions. Future research must prioritise quantitative studies to elucidate causal pathways and long-term impacts, rigorously examining the roles of gender, geography, environment, and comorbidities. Bridging this divide is an essential public health imperative demanding systemic reform.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024516535, identifier PROSPERO [CRD42024516535].